(untitled) (Scientific journal of the Fergana State University, 2023)
In this article the affairs of population census in Uzbekistan SSR (Soviet Socialist Republic) for 1926 have been revealed. The purpose of the Soviet Union from the population census was determined. In 1926, the population of the Turkistan is registered and Central Statistical Committee formed population’s statistics. The final results of the register of the population are analyzed respectively through the published main statistic sources which are regions’ sections.